Human Capital and the Post-Capitalist Ideology - O. A. Podberezkina (Vestnik MGIMO-Universiteta)
The article analyzes the reasons for the lack of a coherent system of views with the Russian elite and society in the development of the country and its place in the modern international relations, the role of LFO in the socio-economic and political transformation of the country, the main features of the ideology that is capable of justify the strategy of Russia's entry into the globalized world.